1999
DOI: 10.1037/0021-843x.108.3.538
|View full text |Cite
|
Sign up to set email alerts
|

Testing Damasio's somatic marker hypothesis with psychopathic individuals: Risk takers or risk averse?

Abstract: Damasio and colleagues (A. R. Damasio, 1994; A. R. Damasio, D. Tranel, & H. Damasio, 1990) have theorized about a possible relationship between somatic markers and the behavior of psychopathic individuals (Ps), but, to date, there are no published data regarding the proposed relationship. The authors assessed 86 Caucasian and 71 African American male offenders using R. D. Hare's (1991) Psychopathy Checklist--Revised and used a modified version of Bechara and colleagues' (A. Bechara, A. R. Damasio, H. Damasio, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
4
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(116 citation statements)
references
References 27 publications
8
101
4
3
Order By: Relevance
“…However, it is worth noting that a recent study investigating boys with psychopathic tendencies found intact performance for simple response reversal [16]. With regard to the gambling task, two studies have reported non-significant differences between psychopathic and comparison groups [12,60]. However, the procedure of both studies differed significantly from those of Bechara et al [6].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, it is worth noting that a recent study investigating boys with psychopathic tendencies found intact performance for simple response reversal [16]. With regard to the gambling task, two studies have reported non-significant differences between psychopathic and comparison groups [12,60]. However, the procedure of both studies differed significantly from those of Bechara et al [6].…”
Section: Discussionmentioning
confidence: 90%
“…Over the course of the task, healthy participants show a preference for the low-risk decks whereas patients with lesions to the OFC continue to choose disadvantageously [2,5]. Two studies have found psychopathic adults to perform similarly to comparison groups on the gambling task [60,12]. However, the studies contained significant procedural differences from those presented by Bechara et al [8].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Psychopaths, under certain contextual demands, also show poor response inhibition Lapierre et al, 1995), response modulation (Newman and Kosson, 1986;Newman et al, 1987Newman et al, , 1992Newman and Schmitt, 1998) and more recently response reversal . Boys with psychopathic tendencies and adult psychopaths tend to show impairments on the Bechara gambling test of decision making (Blair, 2001;Mitchell et al, 2002), though not all studies have found this effect (Schmitt et al, 1999).…”
Section: Neurology and Psychopathymentioning
confidence: 97%
“…The strongest parallels between purported impairments in OFC functions and antisocial behavior have naturally been investigated with the construct of psychopathy (Damasio, 2000;Schmitt, Brinkley, & Newman, 1999).…”
Section: Accounting For Antisocial Behaviorsmentioning
confidence: 99%